ANALISIS KEMAMPUAN BERPIKIR KREATIF SISWA SMK KELAS XI PADA MATERI PERPANGKATAN, BENTUK AKAR DAN LOGARITMA - Hoerul Rahman; Rippi Maya; Puji Nurfauziah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Mathematical creative thinking is the ability to think with the aim of solving a problem with various ideas, generating various ideas, being able to create new ways that are not the same as other people and also being able to develop ideas or ideas. The purpose of this research is to analyze the mathematical creative thinking skills of SMK students in West Bandung with the indicators used consisting of 4 components, such as (1) Fluency; (2) Flexibility; (3) Originality; and (4) Elaboration. This research used a descriptive qualitative method and subject of this research is 10 students in the Vocational High Schools in West Bandung, the instruments used in this study are 5 items of material power, roots, and logarithms. Based on the results of the analysis of the percentage of completeness in this study, it was found that the creative thinking ability of students was still relatively low so further research was needed on students' creative thinking abilities with the aim of producing data that could be used as material for analysis and evaluation in producing what kind of learning model could improve students' mathematical creative thinking skills.